Plays from favorite folk tales : 25 one-act dramatizations of stories children love - Kamerman, Sylvia E. (Boston : Plays, Inc., 1987)
Twenty-five one-act dramatizations of stories from folklore. Includes "Rapunzel," "Aladdin," "King Midas," "Stone Soup," and "Finn McCool.".
8.3
5-8
Keywords: Children's plays, American; Folklore -- Juvenile drama; One-act plays, American; Folklore -- Drama; Plays -- Collections; Drama -- Collections; Folklore -- Drama; One act plays